Early detection of human cytomegalovirus viremia in bone marrow transplant recipients by DNA amplification. - Nolte, F S (1995)
Surveillance blood cultures for human cytomegalovirus (HCMV) are commonly used to identify the bone marrow transplant (BMT) recipients with the highest risk of serious HCMV disease and for whom early interventional ganciclovir therapy would be beneficial. We monitored 36 allogeneic BMT recipients weekly for the presence of HCMV in the blood from 0 to 100 days posttransplantation. Viable HCMV in leukocytes (WBC) was detected by shell vial and tube culture methods. HCMV DNA in WBC and plasma was detected by PCR and DNA hybridization using primers and a probe from the EcoRI fragment D region of HCMV AD169. A uracil-N-glycosylase-dUTP PCR protocol was used to prevent false-positive results due to amplicon carryover. Seventeen patients had multiple consecutive positive samples containing HCMV DNA in plasma or WBC. In 14 of 17 patients, HCMV was also detected by blood culture. HCMV DNA was detected sporadically in six patients, none of whom had positive cultures. One patient had HCMV viremia detected by WBC culture only. The remaining 12 patients had no positive PCR assays or blood cultures. For the patients with positive blood cultures, PCR detection of HCMV DNA in plasma preceded detection of HCMV in culture by a mean of 8 days and detection in WBC preceded detection in culture by 6 days. HCMV disease (interstitial pneumonia) was documented for two patients with viremia (blood culture and PCR positive) and one patient without viremia (blood culture and PCR negative). The earlier recognition of high-risk patients provided by detection of HCMV DNA in plasma or WBC may improve the efficacy of early interventional antiviral therapy.